The voucher promise "Section 8" and the fate of an American neighborhood - Rosen, Eva, 1983- (Book collections on Project MUSE., 2020)
"This book examines the Housing Voucher Choice Program, colloquially known as "Section 8," and the effect of the program on low-income families living in Park Heights in Baltimore. In a new era of housing policy that hopes to solve poverty with opportunity in the form of jobs, social networks, education, and safety, the program offers the poor access to a new world: safe streets, good schools, and well-paying jobs through housing vouchers. The system should, in theory, give recipients access to housing in a wide range of neighborhoods, but in The Voucher Promise, Rosen examines how the housing policy, while showing great promise, faces critical limitations. Rosen spent over a year living in a Park Heights neighborhood, getting to know families, accompanying them on housing searches, spending time on front stoops, and learning about the history of the neighborhood and the homeowners who had settled there decades ago. She examines why, when low-income renters are given the opportunity to afford a home in a more resource-rich neighborhood, they do not relocate to one, observing where they instead end up and other opportunities housing vouchers may offer them"--